Robot‐assisted technique for Boari flap ureteric reimplantation: replicating the techniques of open surgery in robotics. (17th May 2016) - Stolzenburg, Jens‐Uwe; Rai, Bhavan P; Do, Minh; Dietel, Anja; Liatsikos, Evangelos; Ganzer, Roman; Qazi, Hasan; Meneses, Aurus Dourado; Kallidonis, Panagiotis
Abstract : Objective: To describe our robot‐assisted Boari flap ureteric reimplantation (RA‐BFUR) technique, Please see Video S1. Methods: The RA‐BFUR technique is based on the open surgical technique of Übelhör, and the experience includes 11 cases. Results: Excellent results were achieved after a mean follow‐up period of >12 months. Conclusion: The RA‐BFUR technique could be considered a safe and effective method of ureteric reimplantation for long distal ureteric strictures.